PENGARUH KOMUNIKASI TERHADAP KINERJA KARYAWAN CV. BINTANG JAYA ABADI - SUTARNO .; YENNY .; SUPRIYANTO .; DEWI ANGGRAINI; ZULKIFLI UMAR (LP2MTBM MAKARIOZ, 2019)
Organizational performance is a reflection of employee performance, but the employee's performance will be influenced byseveral factors both external and internal. One such factor is communication, based on the condition, the purpose of thisresearch is to know the influence of communication on employee performance. Sample on this study all employees of CV.Bintang Jaya Abadi Medan amounting to 38 people. The research uses quantitative associative methods aimed atmeasuring the influence of free variables on bonded variables, subsequent to the poll results analyzed by data analysistechniques in the form of simple linear regression. The results of the study expressed communication affecting employees 'performance in CV. Bintang Jaya Abadi Medan. The amount of free variable influence on variables is tied to 33.5%, while theremaining 66.5% is influenced by other factors that are not incorporated into the research variable.